PERBANDINGAN MODIFIED CASSAVA FLOUR (MOCAF) DENGAN TEPUNG KACANG HIJAU (Vigna radiate. L) TERHADAP KARAKTERISTIK SPONGE CAKE - Deyana Aprilia, Ni Putu Riska; Yusa, Ni Made; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of comparison between mocaf and green bean flour on the characteristics of sponge cake, and to know the better ratio between mocaf and green bean flour on the characteristics of sponge cake. The experimental design used a randomized block design with one treatment factor. The ratio of green bean flour and mocaf flour, which consists of 6 levels such as: 90% : 10%, 80% : 20%, 70% : 30%, 60% : 40%, 50% : 50%, 40% : 60%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analyzed by analyzed variance and if the treatment had an effect on the variable then continued with Duncan test. The result showed green bean flour and mocaf ratio had a significant effect on water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, unfolding factor,color (hedonic), aroma (hedonic), texture (hedonic and scoring), taste (hedonic), pores uniformity (hedonic and scoring) and overall acceptance (hedonic). Ratio of 40% mocaf and 60% green bean flour had the best characteristics, with 25,65 % water content, 1,17 % ash content, 14,48% protein content, 20,84% fat content, 37,81% carbohydrate content, 5,74% crude fiber content, 44,87% developing power,color rather liked, aroma liked, texture rather soft and liked, taste liked and typical of green beans, pores uniformity liked and rather uniform, and overall acceptance liked.